Changes in interleukin-27 levels in patients with acute coronary syndrome and their clinical significance - Zhang, Lin; Zhang, Junfeng; Su, Shaohong; Luo, Suyan (PeerJ, 2019)
Background This study evaluated changes in interleukin (IL)-27 levels in patients with acute coronary syndrome (ACS) and their influence on Th1, Th2, and Th17 cells. Methods Serum levels of IL-27, IL-4, IL-17, and interferon (IFN)-γ in healthy subjects as well as patients with ACS, including stable angina pectoris (SA), unstable angina pectoris (UA), and acute myocardial infarction (AMI), were determined using an enzyme-linked immunosorbent assay. The proportions of Th1, Th2, and Th17 cells among peripheral blood mononuclear cells (PBMCs), were measured using flow cytometry, after incubation with phorbol myristate acetate (PMA) for 4 h. The proportions of Th1 and Th17 cells among PBMCs in AMI and UA were detected after stimulation with IL-27 or PMA + IL-27 for 4, 8, and 12 h. Results Serum levels of IL-27 in patients with AMI and UA were significantly lower than those in SA and control groups, while serum levels of IL-17 and IFN-γ in AMI and UA groups were dramatically increased compared to those in SA and healthy control groups. However, there were no statistically significant differences in serum IL-4. The proportions of Th1 and Th17 cells among PBMCs were statistically significantly higher in the AMI and UA groups than those in the SA and control groups, while there was no statistically significant difference in the proportion of Th2 cells among different groups. For patients with AMI and UA, the effect of co-stimulation of PBMCs with PMA and IL-27 was not significantly different from that of PMA single stimulation, while PMA + IL-27 co-stimulation lowered the Th17 cell proportion significantly compared to PMA single stimulation. Discussion Compared to SA patients and healthy controls, patients with ACS (AMI + UA) had lower serum levels of IL-27 and higher proportions of PBMC Th1 and Th17 cells, which could be attributed to the inhibitory effects of IL-27 on the proliferation of Th17 cells. These results indicated that IL-27 could be a novel therapeutic target in ACS patients.
Keywords: IL-27; Th2 cells; Acute coronary syndrome